Canadian Contributions to Anabaptist Studies since the 1960s - Seiling, Jonathan R. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
Anabaptist studies in Canada have been marked by an exceptional degree of productive, inter-confessional (or non-confessional) engagement, most notably between Mennonites, Baptists, and Lutherans. The institutions making the greatest contributions have been at the University of Waterloo (including, but not exclusively, Conrad Grebel University College), Queen’s University, and Acadia Divinity College. The geographic expansion of Anabaptist studies beyond the traditional Germanic centres into eastern Europe and Italy, and the re-orientation of analysis away from primarily theological or intellectual history toward a greater focus on socio-political factors and networking, have been particular areas in which Canadian scholars have impacted Anabaptist studies. The relationship of Spiritualism (and later Pietism) to Anabaptist traditions and the nature of Biblicism within Anabaptism, including the greater attention to biblical hermeneutics with the “Marpeck renaissance,” have also been studied extensively by Canadians. International debates concerning “normative” Anabaptism and its genetic origins have also been driven by the past generations of Canadian scholars (monogenesis, polygenesis, post-polygenesis).